Dynamics of picoplankton community from coastal waters to the open sea in the Central Adriatic - ŠANTIĆ, D.; ŠESTANOVIĆ, S.; ŠOLIĆ, M.; KRSTULOVIĆ, N.; KUŠPILIĆ, G.; ORDULJ, M.; GLADAN, Ž. N. (Mediterranean Marine Science, 2013)
<!--[if gte mso 9]> Mike Waring 12.00 <![endif]--> Flow cytometry was used to describe seasonal cycles of Prochlorococcus (Prochl), Synechococcus (Syn), picoeukaryotes and heterotrophic bacteria in the central Adriatic Sea along the trophic gradient from January to December 2010. All picoplankton parameters decreased from eutrophic to oligotrophic areas, while the biomass ratio of bacterial to autotrophic picoplankton showed an increase along the trophic gradient. Bacterial biomass ranged from 5.28 to 21.20 μg C l-1. Increased values were present during warmer seasons with the domination of low nucleic acid (LNA) group of bacteria. The high nucleic acid (HNA) bacterial group dominated during the winter and the spring. Bacterial production ranged from 0.09 -0.45 × 104 cells ml-1 h-1 .At coastal stations increased production was present during the winter and the spring and was more or less uniform at open sea stations. Biomasses of Syn and Prochl ranged from 0.16 to 11.47 µg C-1 l-1 and from 0.01 to 3.08 µg C l-1, respectively. They were elevated during the summer and the autumn at coastal stations and during the late winter at the open sea. Syn biomass always dominated over Prochl participating with 61.6-97.2% in biomass of cyanobacteria. Biomass of picoeukaryotes ranged from 1.21 to 21.85 µg C l-1 and was the highest during the winter. Their biomass notably prevailed in autotrophic picoplankton (APP) biomass over that of picocyanobacteria during the whole year. Autotrophic components (Prochl, Syn and picoeukaryotes) made greater contribution to the picoplankton biomass in mesotrophic and eutrophic areas, while heterotrophic bacteria became more important under oligotrophic conditions. <!--[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Cambria","serif"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Cambria; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-fareast-language:EN-US;} --> <!--[endif] -->